PENGARUH (DER) DEBT TO EQUITY RATIO, CASH RATIO, RETURN ON EQUITY DAN FIRM SIZE TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI TERDAFTAR DI BEI TAHUN 2014-2017 - Gheitsa Fadilla Rahmadhani Siregar; Novelline Novelline; Winny Ivana; Friska Darnawaty Sitorus; Tantri Octora Dwi Syah Putri (Jurnal Akrab Juara, 2019)
The objective of the study is to test and analyze the effect of Debt to Equity Ratio, Cash Ratio, Return on Equity, dan Firm Size on Dividend Payout Ratio, on manufacturing companies in the consumer goods industry sector listed in the Indonesia Stock Exchange on the periode of 2014-2017. The research used some theories of Debt to Equity Ratio, Cash Ratio, Return on Equity, Firm Size and Dividend Payout Ratio. The research was used by a quantitative research approach, this research was causal/clausal. The data collection of this research was performed by study documentation. This research uses secondary data types and sources. The research finding revealed that Debt to Equity Ratio, Cash Ratio, Return on Equity dan Firm Size simultaneously have a positive effect on on Dividend Payout Ratio on manufacturing companies in the consumer goods industry sector listed in the Indonesia Stock Exchange on the periode of 2014-2017. The research concluded that Return on Equity partially have a positive and significant effect on Dividend Payout Ratio on manufacturing companies in the consumer goods industry sector listed in the Indonesia Stock Exchange on the periode of 2014-2017, while the Debt to Equity Ratio, Cash Ratio, and Firm Size partially does not have any significant effect on manufacturing companies in the consumer goods industry sector listed in the Indonesia Stock Exchange on the periode of 2014-2017.